Caractérisation et délimitation de la catégorie des libfixes en anglais - Caroline Marty (Anglophonia)
This paper focuses on the morphological process of libfixation (term coined by Arnold Zwicky). Libfixes are units which have been "liberated" from a source word in order to be used with new bases. Examples are -athon in zumbathon, -licious in bookilicious, -(a)holic in workaholic or -zilla in bridezilla. The extraction of a libfix brings about a morphological reanalysis of the source word, known as recutting. This reanalysis leads to a change in semantic status: as part of the source word, the libfix cannot be considered as a morpheme, but it can be labeled as such after its extraction. It is given a specific meaning and can be used in transparent compositions. For example, the sequence -zilla is not associated with any specific meaning in Godzilla (the denomination is opaque), but it becomes a full-fledged morpheme meaning ‘unpleasing, controlling’ in the schema [noun + -zilla], then perceived as more transparent (bridezilla meaning ‘a controlling bride’). The semantic and syntactic properties of libfixes are studied by comparing forty-nine units that are considered libfixes in the literature (e.g. -gate, -maggedon, -tainment, or those quoted earlier). The data is extracted from the English Web Corpus 2015 (Sketch Engine), the Corpus of Contemporary American English (COCA) and the Corpus of Historical American English (COHA). The productivity of the schemas yielded by libfixes is also considered. I will show that libfixation is a morphological process that generates very productive schemas based on recutting and semantic secretion. From a diachronic perspective, the libfix is first used by speakers to coin new ad hoc expressions, and it then becomes entrenched as a full-fledged construction capable of yielding a series of types.